Pengaruh Variasi Tingkat Daya dan Waktu Pemanasan Microwave terhadap Karakteristik Tepung Jelai (Coix lacryma-jobi L.) - Agustin, Sukmiyati; Mardiatuzzakiah, Ratih (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 9 No 2 (2024), 2025)
Jelai ( Coix lacryma-jobi L.) is a cereal crop belonging to the group of grains (Poaceae). The starch content in jelai plants is very high, around 52%, so it has the potential to be processed into flour. The natural starch found in jelai seeds has the disadvantage that it takes a long time to process and is not resistant to acid treatment. Heating using the microwave method to modified native jelai flour is considered more efficient because it provides faster heating, more homogeneous treatment, and minimizes energy consumption. This study was conducted to determine the effect of power level and microwave heating time on the physicochemical and functional characteristics of jelai flour. This study used a completely randomized design (CRD) with two factors, i.e. power level 20p, 60p. 100p) and heating time (5, 10, 15 minutes) with three replications. This study showed that the variation of microwave power level had a significant effect on bulk density, swelling volume, and solubility, but no significant effect on moisture content and viscosity levels of modified jelai flour. Meanwhile, the variation in microwave heating time has a real effect on solubility, but no significant effect on moisture content, bulk density, swelling volume, and viscosity of modified jelai flour. Microwave power level 20p and heating time of 15 minutes resulted in jelai flour with characteristics closest to wheat flour based on bulk density and solubility value.